Does a graph-intensive economics curriculum promote epistemological access to economic theory? - Marire, J. (South African Journal of Higher Education, 2018)
The paper evaluates whether graph-intensive pedagogic and assessment practices in introductory economics promote student learning. It evaluates the role of instructor-supplied graphs in the correct application and interpretation of graphs. Using simple linear and panel regressions on student assessment data for graph-based multiple choice questions and descriptive analysis based on written student answers, the paper finds that graph-intensive pedagogic and assessment practices hinder student learning and that there are gender and epistemological biases associated with them. While instructor-supplied graphic illustrations offer a solution, findings suggest a contrary adverse effect. Such supplementary materials are necessary but not sufficient in promoting deep learning. Combined with negative marking, graph dominated assessment practices encourage students to avoid answering graph-based questions, which undermines their performance.